Postoperative course and prognostic value of circulating angiogenic cytokines after pancreatic cancer resection - Yang, Cui; Kulu, Yakup (OncoTarget, 2017)
Oncotarget | https://doi.org/10.18632/oncotarget.20315 Cui Yang, Ulrich Bork, Sebastian Schölch, Yakup Kulu, Lars Kaderali, Uta L. Bolstorff, Christoph Kahlert, Jürgen Weitz, Nuh N. Rahbari, Christoph Reissfelder
Published: August 17, 2017
Gesehen am 26.06.2018